The Student SOM Survey 2006 - SOM Institute, University of Gothenburg (University of Gothenburg, 2008)
Student SOM is a survey carried out at the Social Science Faculty at the University of Gothenburg. The questionnaire is divided into five areas: Your university studies, the Bologna process; mass media, politics, and society; activities and interests; and background.

Purpose:

To find out how students feel about their education and the social environment at the University of Gothenburg

Student-SOM 2006 är en undersökning genomförd vid Göteborgs universitets samhällsvetenskapliga fakultet. Undersökningen riktar sig till samtliga nybörjarstudenter i fakultetens olika ämnen och samtliga studenter på fördjupningsnivå eller i slutet av utbildningsprogram. Frågeformuläret består av fem frågeområden: dina universitetsstudier; Bolognaprocessen; massmedier, politik och samhälle; aktiviteter och intressen; samt bakgrund.

Syfte:

Ta reda på hur studenterna uppfattar sin utbildning och den studiesociala miljön vid Göteborgs universitet
SOM-undersökningen till studenter 2006
Student-SOM 2006
Keywords: CORS; CORS; Higher and further education; Gymnasial och högre utbildning; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap